Hourglass‐shaped impedance network based nonelectrolytic capacitors high step‐up converter with low voltage stress. (1st December 2020) - Zhang, Guidong; Chen, Weichen; Yu, Samson S.; El Aroudi, Abdelali
Summary: In this study, a novel high‐step‐up converter is proposed with a new hourglass‐shaped impedance network (HIN). Due to the short lifetime of electrolytic capacitors (ECs), the proposed converter uses nonelectrolytic capacitors (NECs), which however can realize all ECs' features. Besides, the proposed converter has low capacitor voltage stresses, ensuring it could be electrolytic‐capacitors‐free. With this feature, the proposed high step‐up converter has smaller size, lighter weight, smaller parasitic resistance, and longer operation life than the conventional ones with ECs. In this paper, detailed operational principle and performance of the proposed converter are presented, to demonstrate its advanced features. Simulation and experimental studies are also carried out, which validate the feasibility and effectiveness of the proposed converter. Abstract : We propose a novel high‐step‐up converter with a new hourglass‐shaped impedance network (HIN). Due to the short lifetime of electrolytic capacitors (ECs), the proposed converter uses nonelectrolytic capacitors (NECs), which however can realize all ECs' features. Besides, the proposed converter has low capacitor voltage stresses, ensuring it could be electrolytic‐capacitors‐free.